Assessment of redox status in children with attention deficit hyperactivity disorder - Saxena, Anil Kumar; Kukreja, Ruchi; Ali, Bashi; Sitholey, Prabhat; Gurtu, Sunil (2009)
Attention deficit hyperactivity disorder (ADHD) is one of the most common neuro-behavioural disorders in children characterized by hyperactivity, impulsiveness and inattention beyond the norm for a child’s age. Oxidative injury is involved in many neurological disorders, however, not much is known about the possible role of oxidative stress in the pathogenesis of ADHD. The present study was, therefore, designed to evaluate the antioxidant activity (AOA) of ADHD children as compared to age-matched healthy children by monitoring the antioxidant potential of saliva as a biomarker of oxidative stress. The subjects of the study were divided into Group I = Control (n=35); Group II = ADHD patients (n=47). Group II was subdivided into A. Pretreatment group comprising of Hyperactive-impulsive type (ADHD-HI; n=10), Inattentive type (ADHD-I; n=6), Combined type (ADHD-C; n=16) and B. Post-treatment group comprising of Short-term follow-up group (<3 months) and Long-term follow-up group (1-3 years). AOA in the pretreatment group and short-term post-treatment group was found to be significantly lower (0.86 ± 0.07 mM/l, 0.79 ± 0.18 nM/l, respectively) as compared to the control group (1.24 ± 0.08 nM/l). However the mean AOA in the long-term post-treatment group (1.30 ± 0.11 nM/l) did not show any significant difference as compared with the control group. The catalase activity in saliva showed a pattern similar to that of total AOA in the pre-treatment and long-term follow up groups. From the above it can be surmised that there is a decrease in the antioxidant capacity of the body in patients with of ADHD and it tends to recover towards control values after sustained drug therapy. Supplementation with antioxidant may provide additional benefits in these patients.